Perancangan Visualisasi 3D Gedung FTK UNIVERSITAS HARAPAN Medan Dengan Menggunakan Teknologi Virtual Reality Dan Augmented Reality Berbasis Android - Khairul Sani; Ade Zulkarnain Hasibuan; Fera Damayanti (Unit Pengelola Jurnal Universitas Harapan Medan, 2023)
Technological developments are increasingly advanced, one of which is multimedia technology, namely Virtual Reality. With Virtual Reality technology, it can be used as a promotional medium and also to recognize objects in 3D form. With Virtual Reality and Augmented Reality technology, it can be used as a promotional medium and also to recognize objects in 3D form. This research utilizes Virtual Reality and Augmented Reality as promotional media and also as a medium for introducing the FTK environment at Harapan University, Medan. There is minimal information on Unhar's Engineering and Computer faculty for prospective students/community members who want to know the shape of the building and the location of the campus rooms. This application program can help users to find the building and the rooms inside the building, without having to ask the security guard or students who are there. at campus locations, with this technology users can determine their destination without having to be in the campus area first. This application runs on smartphone devices with the Android operating system and has a gyroscope feature. After going through all the testing stages and getting the